Novel insight into circular RNA HECTD1 in astrocyte activation via autophagy by targeting MIR142-TIPARP: implications for cerebral ischemic stroke. Issue 7 (3rd July 2018) - Han, Bing; Zhang, Yuan; Zhang, Yanhong; Bai, Ying; Chen, Xufeng; Huang, Rongrong; Wu, Fangfang; Leng, Shuo; Chao, Jie; Zhang, John H.; Hu, Gang; Yao, Honghong
ABSTRACT: Circular RNAs (circRNAs) are highly expressed in the central nervous system and are involved in the regulation of physiological and pathophysiological processes. However, the potential role of circRNAs in stroke remains largely unknown. Here, using a circRNA microarray, we showed that circular RNA Hectd1 ( circHectd1 ) levels were significantly increased in ischemic brain tissues in transient middle cerebral artery occlusion (tMCAO) mouse stroke models and further validated this finding in plasma samples from acute ischemic stroke (AIS) patients. Knockdown of circHectd1 expression significantly decreased infarct areas, attenuated neuronal deficits, and ameliorated astrocyte activation in tMCAO mice. Mechanistically, circHECTD1 functions as an endogenous MIR142 (microRNA 142) sponge to inhibit MIR142 activity, resulting in the inhibition of TIPARP (TCDD inducible poly[ADP-ribose] polymerase) expression with subsequent inhibition of astrocyte activation via macroautophagy/autophagy. Taken together, the results of our study indicate that circHECTD1 and its coupling mechanism are involved in cerebral ischemia, thus providing translational evidence that circHECTD1 can serve as a novel biomarker of and therapeutic target for stroke. Abbreviations: 3-MA: 3-methyladenine; ACTB: actin beta; AIS: acute ischemic stroke; AS: primary mouse astrocytes; BECN1: beclin 1, autophagy related; BMI: body mass index; circHECTD1 : circRNA HECTD1 ; circRNAs: circular RNAs; CBF: cerebral blood flow; Con: control; DAPI: 4ʹ, 6-diamidino-2-phenylindole; ECA: external carotid artery; FISH: fluorescence in situ hybridization; GAPDH: glyceraldehyde-3-phosphate dehydrogenase; Gdna: genomic DNA; GFAP: glial fibrillary acidic protein; GO: gene ontology; HDL: high-density lipoprotein; IOD: integrated optical density; LDL: low-density lipoprotein; LPA: lipoprotein(a); MAP1LC3B: microtubule-associated protein 1 light chain 3 beta; MIR142 : microRNA 142; mNSS: modified neurological severity scores; MRI: magnetic resonance imaging; NIHSS: National Institute of Health Stoke Scale; OGD-R: oxygen glucose deprivation-reperfusion; PCR: polymerase chain reaction; PFA: paraformaldehyde; SQSTM1: sequestosome 1; TIPARP: TCDD inducible poly(ADP-ribose) polymerase; tMCAO: transient middle cerebral artery occlusion; TTC: 2, 3, 5-triphenyltetrazolium chloride; UTR: untranslated region; WT: wild type